Construction of a narrative instrument for government investment - Marius Clemens; Claus Michelsen; Malte Rieth (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
The article documents the construction of a narrative instrument for government investment, used in the paper 'An Estimation and Decomposition of the Government Investment Multiplier'.
Keywords: E62; E65; H54; 330; Fiscal policy; public investment; structural vector autoregression; instrumental variable; general equilibrium model; Germany